FAKTOR YANG MEMPENGARUHI IBU DALAM KUNJUNGAN IMUNISASI PADA MASA PANDEMI COVID-19 DALAM PERSPEKTIF HEALTH BELIEF MODEL (HBM) - Nani Susilowati; Titik Sapartinah; Erna Widyastuti (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
Pandemic Covid-19 has an impact on the implementation of health programs, especially immunization services and PD3I surveillance. Coverage of immunization at Kaliwungu health center is still low, especially polio (89.3%) compared to 23 other health centers in Semarang regency and immunization visits only 3.2% in March. The purpose of the study was to determine the factors that influenced immunization visits during the Covid-19 pandemic period based on the health belief model (HBM) theory at Kaliwungu health center. This research is observational analytic research with a maternal population who has a baby aged 1-12 months, a total of 370 people and a sample of 80 people. The results of the univariate analysis of the Chi Square test of vulnerability and high seriousness 51.2%, perception of cues to action high 58.8%, high benefit perception of 72.5%, high barrier perception of 46.3%, and active immunization visits 66.3%, Bivariate analysis of perception of vulnerability and seriousness (p value 0.001), perception of benefits (p value 0.009), perception of barriers (p value 0.009) and perception cues to action (p value 0.169). The conclusion of the study is that there is a relationship between the vulnerability and seriousness of the disease, benefits and obstacles with immunization visits. While the perception of cues to action has no relationship with immunization visits during the Pandemic Covid-19 period. Advice for health workers to improve information services and immunization health promotion during Covid-19.